An exploratory and descriptive study on political persuasion and the extent to which it influence citizen voting behaviour. - Jooste, Chanté (The IIE, 2019)
It is argued that political persuasion can be used as a powerful tool to influence and guide citizen voting decisions and behavior (Anthem Branding, 2018). The main focus of this research study is to explore and describe political persuasion and the extent to which it influence citizen voting behaviour. This research topic was specifically explored in a South African context. In order to explore and describe the influence of political persuasion on voting behaviour, the researcher made use of a mixed method research approach. Along with using a mixed method approach to conducting research, the researcher made use of a mixed method analysis. For the purpose of qualitative data, the researcher made use of thematic analysis in order to identify themes within the collected data. A mixed method approach allowed the researcher to analyse quantifiable data through the use of pie charts. The findings of the research study reveal that political persuasion influence citizen voting behaviour to a significant degree with regards to considered factors.
Keywords: Political persuasion; Voting behaviour; Brand strategy; Brand communication; Brand awareness; Brand